The Effectiveness of Traditional Congklak Game To Improve Counting Skills Elementary School Children - Lutfiah, Duri; Lestari, Salwa Gita; Ananda, Deva Teja; Annisa, Nida Muthi; Nurhasanah, Fitriani; Supriatna, Anggun Zachra Julaiha (International Journal of Ethno-Sciences and Education Research, 2025)
The low counting skills of first-grade students at SDN Tarumsari are often associated with monotonous learning methods and the lack of use of concrete media that suits their cognitive development stage. This study aims to examine the effect of traditional congklak games on the counting skills of first-grade elementary school students. The study employed a quasi-experimental method with a one-group pretest-posttest design. Eight students (four males and four females) were selected through purposive sampling based on their numeracy abilities. The instrument used was a simple math test. The results showed a significant difference between the mean scores of the pretest (95.13) and posttest (92.63) based on the paired sample t-test with a significance value of 0.028 (p < 0.05). Although the posttest score was slightly lower statistically, it still indicates that the use of congklak was able to provide cognitive stimulation involving concrete activities and direct interaction, which had an impact on students' counting skills.